f2f and cyberbullying among children in Northern Ireland: Data from the Kids Life and Times Surveys - MC GUCKIN, CONOR (My University, 2010)
Comparatively little is known about the nature, incidence and correlates of bully/victim problems in the Northern Ireland school system. The present study examined the prevalence of self-reported experiences of bully/ victim problems (f2f and cyber), and the relationship between such experiences and levels of psychological wellbeing among representative samples of primary school pupils who participated in the 2008 and 2009 `Kids Life and Times Survey? (ARK, 2008, 2009). Bully/victim problems among these children were pervasive. Personal experience of involvement in bully/victim problems was associated with impaired psychological well-being. Findings are interpreted within the context of previous data from Northern Ireland and the wider international literature on bully/victim problems.
PUBLISHED
Keywords: Cyberbullying